Naipaul’s Divided Self in An Area of Darkness - Nepal, Khagendra Prasad (KMC Research Journal, 2022)
This paper seeks to analyze V.S. Naipaul’s futile attempt of seeking his lost identity in particular reference to his travelogue An Area of Darkness. This study shows how he fails in grabbing the self identity as an Indian and how he diverts himself from his quest when he has time and again suffered by the memory of past. The study adopts qualitative methodology and takes memory studies as a theoretical tool to interpret and analyze the primary text. Moreover, the study focuses on analysis of the text in concern with seeking the fundamental identity that once was lost being a migrant to a distance land. The writer falls in the prey of his own memory time and again and finds himself distorted and distanced from his identity as he is seeking his Indianness there. The study argues that Naipaul remains neither Indian nor Trinidanian due to his own divided cultural and individual self that he possesses in his undying memory.